Spatial Intelligence and Students’ Achievement to Support Creativity on Visuospatial-Based Learning (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This research intended to know how the spatial intelligence and students' achievement support the creativity of prospective student teachers. This study was conducted on the subject of plant anatomy with visuospatial-based learning. The visuospatial-based learning model used in this study is called the wimba learning model. The method of this research was a quantitative /quasi-experiment with the pre- and post-test group design. The population was fourth-semester students in four classes of Biology Education who took Plant Anatomy course in 2017 in a university situated a small town, West Java, Indonesia. The sample of this research was two classes picked using the purposive sampling regarding their homogenous sampling of having the same relative ability. The treatments for each class was that the use of the deductive and inductive approach. The variables measured were spatial intelligence, students’ achievement and creativity of TCIA (Test of Creative Imagery Abilities). The data processing adopting multiple correlation tests with SPSS was to see the relationship between the variables. The results showed that spatial intelligence and students’ achievement could support creativity at a moderate level, indicated by the value of Rdeductive = 0,451 and Rinductive = 0,474, Rinductive Rdeductive, which meant that the inductive approach was better to support creativity. In conclusion, spatial intelligence and students’ achievement could support creativity, especially the inductive approach. The results of this study could be useful to improve the creativity of prospective biology teachers.